Disintegrated Market Orientation and Firm Performance: Moderating Effect of Entrepreneurial Orientation - Jawad Hussain (Journal of Accounting and Finance in Emerging Economies, 2021)
The interplay between strategic orientations has received limited attention in manufacturing small and medium enterprises (SMEs).The existing studies have repeatedly called for investigating the impacts of multiple strategic orientations on organizational performance. Moreover, prior research called for disintegrating the strategic orientation and assessing their effects on organizational performance. Thus, this study is the first of its nature – disintegrating the market orientation (MO) construct and using data from 213 SMEs of Pakistan, collected through survey method, which reports on how the deployment of entrepreneurial orientation (EO) as moderator produces synergistic effect and strengthens the MO dimensions –organizational performance links. The results indicate that the MO dimensions are positively and significantly related to organizational performance. Moreover, EO significantly and positively moderates the MO dimensions and organizational performance relationships. The study provides avenues for future research.